Mekanisme Pelaksanaan Program PKK Di Kelurahan Batunadua Jae Berdasarkan PERMENDAGRI No. 36 Tahun 2020 - Ririn Wahyuni; Ahmatnijar Ahmatnijar (Jurnal El-Thawalib, 2023)
This study discusses the Strategy and Mechanism of the Family Welfare Empowerment Movement (PKK) in Implementing 10 PKK Main Programs in Batunadua Jae Village, Padangsidimpuan District, Batunadua. This research was motivated by the problems that occurred in Batunadua Jae Village regarding stunting that occurred in children. This type of research is a field research using a conceptual, juridical sociological and legislative approach, namely, Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 36 of 2020 concerning Movement and Empowerment of Family Welfare Article 39, Primary data sources are data obtained directly through interviews with PKK management and the community of Batunadua Jae Village, secondary data sources are journal books and documents related to this research, data collection techniques are by means of observation, interviews, and documentation then descriptive type data analysis techniques This research describes completely in a language so that an understanding in the field between reality and language. The results of this study conclude that the strategies carried out by the PKK movement in implementing the main health programs and health planning for toddlers are, nutritional checks, immunizations, weighing toddlers, giving vitamins, and measuring children's height. immediately notify the community to come to the posyandu. The supporting factor in implementing the main program is the enthusiasm and support of the community and the obstacles are the lack of funds and the lack of community participation.